Designing Aqueous Organic Electrolytes for Zinc–Air Batteries: Method, Simulation, and Validation. Issue 10 (30th January 2020) - Clark, Simon; Mainar, Aroa Ramos; Iruin, Elena; Colmenares, Luis César; Blázquez, Jose Alberto; Tolchard, Julian Richard; Jusys, Zenonas; Horstmann, Birger
Abstract: Aqueous zinc–air batteries (ZABs) are a low‐cost, safe, and sustainable technology for stationary energy storage. ZABs with pH‐buffered near‐neutral electrolytes have the potential for longer lifetime compared to traditional alkaline ZABs due to the slower absorption of carbonates at nonalkaline pH values. However, existing near‐neutral electrolytes often contain halide salts, which are corrosive and threaten the precipitation of ZnO as the dominant discharge product. This paper presents a method for designing halide‐free aqueous ZAB electrolytes using thermodynamic descriptors to computationally screen components. The dynamic performance of a ZAB with one possible halide‐free aqueous electrolyte based on organic salts is simulated using an advanced method of continuum modeling, and the results are validated by experiments. X‐ray diffraction, scanning electron microscopy, and energy dispersive X‐ray spectroscopy measurements of Zn electrodes show that ZnO is the dominant discharge product, and operando pH measurements confirm the stability of the electrolyte pH during cell cycling. Long‐term full cell cycling tests are performed, and rotating ring disk electrode measurements elucidate the mechanism of oxygen reduction reaction and oxygen evolution reaction. The analysis shows that aqueous electrolytes containing organic salts could be a promising field of research for zinc‐based batteries, due to their Zn 2+ chelating and pH buffering properties. The remaining challenges including the electrochemical stability of the electrolyte components are discussed. Abstract : Zinc–air batteries provide low‐cost energy storage. Near‐neutral aqueous electrolytes solve the CO2 absorption problem, but suffer from pH instability and the precipitation of mixed zinc salts during cell operation. Herein, a theory‐based method is presented and validated to identify aqueous electrolytes containing organic salts that support a stable pH and precipitate ZnO.